Causes of Changes in Resistor Resistance Values in Wheatstone Bridge Circuits - Apriliyanto, Sandi; Susilo; Mahindra Abhiyaksa; Mohamad Zainal Roisul Amin (Journal of Educational Engineering and Environment, 2023)
The Wheatstone bridge is an arrangement of electrical circuits for measuring a resistance of unknown magnitude. Applying the Wheatstone Bridge theory in the form of a series of electronic components consisting of resistors and strain gauges. In this study, resistors are used which are passive electronic components that have the property of inhibiting electric current. This aims to determine the value of the resistance loss produced by resistors that are used using several different values. Based on the study, it was found that the theoretical resistor is 150Ω after going through the measurement, it turns out to be 120Ω with a resistance loss of 20%, the 560Ω resistor after going through the measurement, it turns out to be 340Ω with a resistance loss of 39%, the 1000Ω resistor after going through the measurement, it turns out to be 570Ω with a resistance loss worth 47%, the resistor is worth 330Ω after going through the measurement it turns out to be worth 220Ω with a resistance loss of 20%, the resistor is worth 100Ω after going through the measurement it turns out to be worth 80Ω with a resistance loss of 20%. Based on the calculations, the difference in value is obtained between theoretical calculations and using measuring instruments. This is due to several factors, namely measuring instruments that are less valid so that it is necessary to carry out a validation test of the tool and the type of component being measured must be in a stable state. The resistance loss resulting from this study is due to several of these factors.